Development Diplomacy as a Part of Public Diplomacy in the Pursuit of Foreign Policy Aims: Case of European Union Aid to Africa - Dionise, Arakaza (European Scientific Journal, ESJ, 2020)
This paper examines how the European Union and other Western countries use the development aid to pursue their own interests. The paper presents an argument of how development aid is used to protect the citizens of donor countries and their properties in foreign countries. The argument details how the EU and the developed countries use development aid to promote their values and political ideologies linked with public diplomacy. The analysis focuses on the conditions given to beneficiary countries before receiving foreign aid. It also examines the behaviour of recipient nations in regard to supporting their donors. The researcher used the qualitative methodology by means of explanatory research to narrow the broad assumptions related to the research topic. The usefulness of the exploratory research approach relies on its appropriateness in analysing vast quantities of qualitative data by organising the data into specific themes that are recurrent in the data (Bearman, 2013). Exploratory research also helped the author to be creative in order to gain the most amount of insight on a subject as focused on theory building (Opoku, 2016). Secondary data from books, peer reviewed journals, and relevant government and OECD reports were applied to come out with the the findings. Data collected was analysed by applying a thematic approach due to the potential subjective nature of the qualitative data. Conclusion and recommendations were also given.